'To see clearly': John Dos Passos and vision. Issue 7 (2nd July 2020) - Murray, Alex
ABSTRACT: The work of John Dos Passos has been recognised for its acute visual qualities, and for the revolutionary use of the Camera Eye sections of his U.S.A . trilogy to capture subjective seeing. Most scholarship emphasises the role that cinema and modernist art played in the develop of Dos Passos's unique approach to vision, yet this essay argues there is a more fundamental source for vision in his novels: the author's treatment for visual impairment. The essay traces the influence that W. H. Bates's method for correcting visual impairment had on Dos Passos's novelistic craft, drawing on hitherto unexamined notes of the novelist on visual training.